Enhancing Indonesian EFL Learners’ Speaking Skills through Digital Storytelling based on Local Folktales - Ainol Mardhiah; Nurul Kamaliah; Helmiyadi Helmiyadi; Lathifatuddini Lathifatuddini (SAGA: Journal of English Language Teaching and Applied Linguistics, 2024)
This study investigates the effectiveness of enhancing Indonesian English as a Foreign Language (EFL) learners’ speaking skills through digital storytelling grounded in local folktales. The study, which was conducted among first-year university students at Universitas Bumi Persada consisting of 8 people, used a case study. The information was gathered by observing the lecturer who integrated both digital storytelling and local folktales into her instruction in the classroom. To gain more comprehensive data and in-depth information, students were also interviewed regarding their experiences and opinions. The study explores the integration of digital storytelling techniques with traditional local folktales to foster speaking proficiency among EFL students. The research intends to provide significant insights into creative language teaching methodologies by leveraging technology and local culture. The findings show that digital storytelling has a considerable impact on students' speaking ability, providing light on the possibilities of adding culturally rich narratives into language teaching. This study adds to the pedagogical discourse by highlighting the potential of digital storytelling as a catalyst for enhancing speaking abilities, particularly among EFL university students in Indonesia.